Pengelolaan Surat Masuk dan Surat Keluar Dengan Menggunakan Aplikasi Manajemen Surat Korporat Untuk Memperlancar Proses Administrasi di PT PLN (Persero) UID Jawa Barat - Carina Mutiara Putri; Sofiatiningsih Sofiatiningsih (Akademi Sekretari Manajemen Taruna Bakti, 2021)
The rapid development of technology in the digital age has a very big impact in changing the way work from manual to computerized, one of the perceived changes in electronic mail. Aplikasi Manajemen Surat Korporat is one application that can speed up the process of handling incoming and outgoing mail. The purpose of this research is to study the process of managing incoming and outgoing mail using Aplikasi Manajemen Surat Korporat to facilitate the administrative process at PT PLN (Persero) UID West Java. This study used qualitative research methods. Data collection techniques carried out by interviewing, observing, documenting with branches of the Secretariat unit, and studying literature from books, journals, and documents relating to research discussions. The results showed that the management of incoming and outgoing mail using Aplikasi Manajemen Surat Korporat in PT PLN (Persero) UID West Java was good, the application used was digital by the times, the system was easy to work on, easy to learn, saving costs, fast, guaranteed security, could distributing information quickly so that every incoming and outgoing mail can be processed quickly, ultimately the service to the public can be improved. Some obstacles are common in nature is the occurrence of disruptions on the internet network that can be overcome when the network improves again